Evaluation of pectinolytic activities for oenological uses from psychrotrophic yeasts. (28th May 2013) - Sahay, S.; Hamid, B.; Singh, P.; Ranjan, K.; Chauhan, D.; Rana, R.S.; Chaurse, V.K.
Abstract: Of the twenty‐three morphotypes of yeasts isolated from soil capable of utilizing pectin as sole carbon source at 6°C, two yeast isolates, one psychrotolerant (PT1) and one psychrophilic (SPY11), were selected according to their ability to secrete pectinolytic enzymes under some oenological conditions (temperature 6 and 12°C and pH 3·5) and ability or inability to grow above 20°C, respectively. As compared to their optimal activity, the three pectinolytic enzymes viz., pectin methyl esterase (PME), endopolygalacturonase (endo‐PG) and exopolygalacturonase (exo‐PG) isolated and assayed at pH 3·5 from PT1 were found to retain 39, 60 and 60% activity at 12°C and 40, 79 and 74% activity at 28°C, respectively. Likewise, the enzymes PME and endo‐PG at pH 3·5 from SPY11 displayed 46 and 86% activity at 12°C and 50 and 60% activity at 28°C, respectively. All these enzymes showed 20–90% of residual activity at pH 3·5 and 6°C. The yeast isolates PT1 and SPY11 were identified as Rhodotorula mucilaginosa and Cystofilobasidium capitatum, respectively, on the basis of morphological, physiological and molecular characteristics. This study presents the first report on pectinolytic activities under major oenological conditions from psychrotolerant isolate R. mucilaginosa PT1 and psychrophilic isolate C. capitatum SPY11. Significance and Impact of the Study: The cold‐active pectinolytic enzymes (PME, endo‐PG and exo‐PG) from the newly isolated and identified psychrophilic yeast Cystofilobasidium capitatum SPY11 and psychrotolerant yeast Rhodotorula mucilaginosa PT1that exhibited 50–80% of their optimum activity under some major oenological conditions pH (3·5) and temperatures (6 and 12° C) could be applied to wine production and juice clarification at low temperature. The psychrotrophic yeasts themselves could be applied to cold process for the production of enzymes thus saving cost of energy and protecting process from contamination. Abstract : Significance and Impact of the Study: The cold‐active pectinolytic enzymes (PME, endo‐PG and exo‐PG) from the newly isolated and identified psychrophilic yeast Cystofilobasidium capitatum SPY11 and psychrotolerant yeast Rhodotorula mucilaginosa PT1that exhibited 50–80% of their optimum activity under some major oenological conditions pH (3·5) and temperatures (6 and 12° C) could be applied to wine production and juice clarification at low temperature. The psychrotrophic yeasts themselves could be applied to cold process for the production of enzymes thus saving cost of energy and protecting process from contamination.